Magnetic Resonance of Impurities, Intrinsic Defects and Dopants in ZnO - Stehr, J. E.; Meyer, B. K.; Hofmann, D. M. (Applied magnetic resonance, 2010)
In the last years an increasing technological interest in the wide band gap semiconductor ZnO has widely stimulated research on this material. The electrical and optical properties of ZnO are strongly affected by the presence of defects and dopant. For instance, to obtain p -type conductivity it requires not only to find a suitable doping element but also to suppress counteracting intrinsic defects. Magnetic resonance experiments can contribute considerable knowledge to this subject. We review the current knowledge on impurities, intrinsic defects and doping elements in ZnO as obtained by magnetic resonance experiments in this paper.